2017
DOI: 10.3390/insects8020038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Conditions for Successful Aphid Control by Ladybirds in Greenhouses

Abstract: As part of my research on the mass production and augmentative release of ladybirds, I reviewed the primary research literature to test the prediction that ladybirds are effective aphid predators in greenhouses. Aphid population reduction exceeded 50% in most studies and ladybird release rates usually did not correlate with aphid reduction. The ratio of aphid reduction/release rate was slightly less for larvae than adults in some studies, suggesting that larvae were less effective (than adults) in suppressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 80 publications
2
26
0
2
Order By: Relevance
“…Failures of aphid control have been associated, among others, with the tendency of the adult beetles to fly away from the host plants soon after release, whether in greenhouses (H€ am€ al€ ainen, 1977), urban trees (Brakefield, 1984), or outdoor crops (Kieckhefer & Olson, 1974). Experimental work has shown that flightless morphs of several species, as obtained by diverse methods, have a longer residence time on host plants and can improve aphid control (Ignoffo et al, 1977;Ferran et al, 1998;Tourniaire et al, 1999;Weissenberger et al, 1999;Lommen et al, 2008;Seko et al, 2008;Adachi-Hagimori et al, 2011;Iguchi et al, 2012; but see Riddick, 2017). Experimental work has shown that flightless morphs of several species, as obtained by diverse methods, have a longer residence time on host plants and can improve aphid control (Ignoffo et al, 1977;Ferran et al, 1998;Tourniaire et al, 1999;Weissenberger et al, 1999;Lommen et al, 2008;Seko et al, 2008;Adachi-Hagimori et al, 2011;Iguchi et al, 2012; but see Riddick, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failures of aphid control have been associated, among others, with the tendency of the adult beetles to fly away from the host plants soon after release, whether in greenhouses (H€ am€ al€ ainen, 1977), urban trees (Brakefield, 1984), or outdoor crops (Kieckhefer & Olson, 1974). Experimental work has shown that flightless morphs of several species, as obtained by diverse methods, have a longer residence time on host plants and can improve aphid control (Ignoffo et al, 1977;Ferran et al, 1998;Tourniaire et al, 1999;Weissenberger et al, 1999;Lommen et al, 2008;Seko et al, 2008;Adachi-Hagimori et al, 2011;Iguchi et al, 2012; but see Riddick, 2017). Experimental work has shown that flightless morphs of several species, as obtained by diverse methods, have a longer residence time on host plants and can improve aphid control (Ignoffo et al, 1977;Ferran et al, 1998;Tourniaire et al, 1999;Weissenberger et al, 1999;Lommen et al, 2008;Seko et al, 2008;Adachi-Hagimori et al, 2011;Iguchi et al, 2012; but see Riddick, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced flight ability in predaceous ladybird beetles has therefore received the interest of researchers over decades (Lommen, 2013). Experimental work has shown that flightless morphs of several species, as obtained by diverse methods, have a longer residence time on host plants and can improve aphid control (Ignoffo et al, 1977;Ferran et al, 1998;Tourniaire et al, 1999;Weissenberger et al, 1999;Lommen et al, 2008;Seko et al, 2008;Adachi-Hagimori et al, 2011;Iguchi et al, 2012; but see Riddick, 2017). A flightless strain of Harmonia axyridis Pallas is commercially available in Japan (MAFF, 2014) but this species has recently been banned from commercial use outside its native range due to its invasiveness (van Lenteren et al, 2008;Roy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…predators and parasitoids) of the hemipterans with their aggressive behaviors (e.g. Bartlett 1961;Banks 1962;Bristow 1984;Cushman & Whitham 1989;Itioka & Inoue 1996;Riddick 2017). However, various species of insect enemies are capable of exploiting hemipterans that ants are guarding, through avoiding aggressions of the ants behaviorally, morphologically and chemically (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ladybirds are effective in the biocontrol of aphid (Hoki et al ., 2014) and in greenhouse settings (Riddick, 2017), and their footprints are known to elicit avoidance behaviour in aphids (Ninkovic et al ., 2013). Phloem-feeding plant parasites, such as aphids, mainly chemically detect the presence of ladybird, e .…”
Section: Introductionmentioning
confidence: 99%